2014
DOI: 10.1007/s11999-013-3229-7
|View full text |Cite
|
Sign up to set email alerts
|

High Level of Residual Symptoms in Young Patients After Total Knee Arthroplasty

Abstract: Background TKA is among the fastest growing interventions in medicine, with procedure incidence increasing the most in younger patients. Global knee scores have a ceiling effect and do not capture the presence of difficulty or dissatisfaction with specific activities important to patients. Questions/purposes We quantified the degree of residual symptoms and specific functional deficits in young patients who had undergone TKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
139
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(147 citation statements)
references
References 9 publications
2
139
0
6
Order By: Relevance
“…Although TKA continues to be effective in providing pain relief and improved function in the majority of patients with degenerative joint disease [26,28,44], recent studies have demonstrated a high percentage of patients undergoing TKA to experience residual symptoms and dissatisfaction [9,[33][34][35]. Furthermore, because the volume of TKAs is disproportionately increasing in younger patients, function and satisfaction in this group of patients becomes even more important [23,43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although TKA continues to be effective in providing pain relief and improved function in the majority of patients with degenerative joint disease [26,28,44], recent studies have demonstrated a high percentage of patients undergoing TKA to experience residual symptoms and dissatisfaction [9,[33][34][35]. Furthermore, because the volume of TKAs is disproportionately increasing in younger patients, function and satisfaction in this group of patients becomes even more important [23,43].…”
Section: Discussionmentioning
confidence: 99%
“…If a second refusal occurred, no further attempts were made. The final data were sent from the UWSC through a secure web site in SPSS format (Version 16.0; SPSS Inc, Chicago, IL, USA) [34].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to gait analyses and biomechanical studies, patients require at least 83°of flexion to ascend stairs, 90°to 100°to descend stairs, 93°to 105°to rise from a standard or short chair, and more than 115°to squat or kneel [3,11,13]. However, up to 20% of patients may develop knee stiffness and achieve knee flexion of less than 90°after their index arthroplasty [12,17,19,28]. If left untreated, knee stiffness reduces the functional outcomes of patients including their daily living activities and satisfaction [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Although the results of classic TKA designs have been previously reported as excellent with a 93% survival rate at 15 years [3], recent studies focusing on patient satisfaction as the primary outcome measure have been less encouraging, with the Ontario Joint Registry showing that only 70% of patients met their expectations one year after TKA [4]. This "un-satisfaction" rate is also higher in younger individuals requiring early intervention because of severe knee osteoarthritis: Parvizi et al [5] reported only 66% of young patients (< 60 years) indicating their knees feeling normal at 1 to 4 years after primary TKA. Because of these reports, in recent years, several manufacturers have implemented specific design modifications in the attempt to improve patient outcomes: between those modifications, highflexion femoral components and increased modularity (femoral, tibial, polyethylene thickness and patellar sizes) have captured particular attentions by many designers.…”
Section: Introductionmentioning
confidence: 99%